Respuestas
¿Demasiados anuncios?Esta es una pregunta difícil y la solución es algo no evidente. Sabemos que \lim_{x \to 0}\frac{f(ax) - f(x)}{x} = b and hence f(ax) - f(x) = bx + xg(x) where g(x) \a 0 as x \to 0. Replacing x by x/a we get f(x) - f(x/a) = bx/a + (x/a)g(x/a) Replacing x by x/a^{k - 1} we get f(x/a^{k - 1}) - f(x/a^{k}) = bx/a^{k} + (x/a^{k})g(x/a^{k}) Adding such equations for k = 1, 2, \ldots, n we get f(x) - f(x/a^{n}) = bx\sum_{k = 1}^{n}\frac{1}{a^{k}} + x\sum_{k = 1}^{n}\frac{g(x/a^{k})}{a^{k}} Letting n \to \infty and using sum of infinite GP (remember it converges because |a| > 1) and noting that f is continuous at x = 0, we get f(x) - f(0) = \frac{bx}{a - 1} + x\sum_{k = 1}^{\infty}\frac{g(x/a^{k})}{a^{k}} Dividing by x and letting x \a 0 we get f'(0) = \lim_{x \to 0}\frac{f(x) - f(0)}{x} = \frac{b}{a - 1} + \lim_{x \to 0}\sum_{k = 1}^{\infty}\frac{g(x/a^{k})}{a^{k}}
La suma \sum_{k = 1}^{\infty}\frac{g(x/a^{k})}{a^{k}} tends to 0 as x \to 0 because g(x) \a 0. The proof is not difficult but perhaps not too obvious. Here is one way to do it. Since g(x)\a 0 as x \to 0, it follows that for any \epsilon > 0 there is a \delta > 0 such that |g(x)| < \epsilon for all x with 0 <|x| < \delta. Since |a| > 1 it follows that |x/^{k}| < \delta if |x| < \delta and therefore |g(x/a^{k})| < \epsilon. Thus if 0 < |x| < \delta we have \left|\sum_{k = 1}^{\infty}\frac{g(x/a^{k})}{a^{k}}\right| < \sum_{k = 1}^{\infty}\frac{\epsilon}{|a|^{k}} = \frac{\epsilon}{|a| - 1} and thus the sum tends to 0 as x \to 0.
Por lo tanto f'(0) = b/(a - 1).
Por CIERTO, el resultado de la pregunta se mantiene incluso si 0 < |a| < 1. Deje c = 1/a, de modo que |c| > 1. Ahora tenemos \lim_{x \to 0}\frac{f(ax) - f(x)}{x} = b implies that \lim_{t \to 0}\frac{f(ct) - f(t)}{t} = -bc (just put ax = t). Hence by what we have proved above it follows that f'(0) = \frac{-bc}{c - 1} = \frac{b}{a - 1} Note that if a = 1 then b = 0 trivially and we can't say anything about f'(0). And if a = -1 then f(x) = |x| provides a counter-example. If = 0 then the result holds trivially by definition of derivative. Hence the result in question holds if and only if || a \neq 1.